Presence of tidal current and wave energy in planned smart grid systems on turkey - TEMİZ, İSMAİL (My University, 2021)
As in many countries around the world, the tendency towards usage of clean and renewable energy sources continues in Turkey to leave more liveable world to the future generations. In this study, the current integration of tidal power and wave energy technologies, which are infinite and renewable energy sources, in smart grid systems on our country and the advantages that these technologies can provide in the future have been examined.
Keywords: smart grid; tidal current; wave energy; renewable energy